Sequence-Structure Based Comparison of Structurally Homologous Thermophilic and Mesophilic Polyethylene Terephthalate (PET) Hydrolases - Hasan, Khomaini; Ulfah, Maria; Nurhayati, Niknik; Sabbathini, Gabriela Christy; Wulandari, Sri Rezeki; Putra, I Gede Eka Perdana; Helianti, Is (Bogor Agricultural University, Indonesia, 2024)
Protein structure has a direct impact on thermostability. Deviations in the primary sequence can affect structural changes, leading to alterations in thermostability properties. However, the molecular basis of protein thermostability is unspecified; thus, elucidation of key factors that role particular protein thermostability is required when engineering proteins to be thermostable. To address this challenge, the amino acid composition, hydrophobicity/hydrophilicity ratio, cysteine bridges, and intrinsic features of two structurally homologous but different thermostability, poly(ethylene terephthalate) hydrolase (PETase) were compared. According to the findings, thermostable and thermolabile PETases have similar folds, compactness, and disulfide bridges. Interestingly, an abundance gap of aromaticity, hydrophobic cluster area, polar amino acid and hydrogen bond network compositions demonstrated dominant trends of variations for both PET hydrolases, indicating a pivotal role of these features in the thermostability of PET hydrolase. Furthermore, increased hydrophobic amino acid frequency in the inner surface of thermostable proteins contributed significantly to thermostability by forming more internal hydrophobic interactions and a less hydrophobic patch. There are no consistent trends in insertions and deletions between both PETases. Taken together, these observations demonstrate that hydrophobicity and hydrogen bond networks are essential factors in thermostability of thermostable PETase.